Gold nanobipyramid@copper sulfide nanotheranostics for image-guided NIR-II photo/chemodynamic cancer therapy with enhanced immune response. (1st March 2023) - Chen, Yiyu; Liu, Ping; Zhou, Chunze; Zhang, Tao; Zhou, Tianxing; Men, Dandan; Jiang, Guihua; Hang, Lifeng
Abstract: Photothermal therapy (PTT), photodynamic therapy (PDT), and chemodynamic therapy (CDT) can cause cancer cell death through an immunogenic process. However, the study of second near-infrared window (NIR-II)-triggered PTT and PDT combined with CDT to induce an immune response has not been recently reported. Here, we integrated gold nanobipyramids and copper sulfide in a core/shell architecture (AuNBP@CuS). The material displays both photodynamic and photothermal properties under irradiation with a NIR-II laser. The released Cu 2+ from CuS under an acidic tumor microenvironment can be converted to Cu + by glutathione following a Fenton-like reaction with hydrogen peroxide to generate highly toxic hydroxyl radicals in the tumor region. Both in vitro and in vivo results demonstrated that such multifunctional nanoplatforms could achieve enhanced efficiency for image-guided tumor suppression based on the NIR-II photo/chemodynamic therapy. We found that damage-associated molecular pattern molecules such as adenosine triphosphate, pre-apoptotic calreticulin, and high mobility group box-1 in dying cells induced by the NIR-II photo/chemodynamic therapy could simultaneously trigger adaptive immune responses. This is the first report revealing that NIR-II photo/chemodynamic therapy based on AuNBP@CuS had promising performance on tumor suppressor with an effective immunogenic cell death process. Statement of significance: 1. AuNBP@CuS displays both NIR-II photodynamic and photothermal properties. 2. Cu + following a Fenton-like reaction to generate highly toxic hydroxyl radicals. 3. The NIR-II photo/chemodynamic therapy can trigger adaptive immune responses. 4. Such multifunctional nanoplatforms could achieve enhanced efficiency for tumor suppression. Graphical Abstract: Image, graphical abstract